Whole-transcriptome analysis of aluminum-exposed rat hippocampus and identification of ceRNA networks to investigate neurotoxicity of Al - Chanting He; Xiaoyan Zhao; Yang Lei; Jisheng Nie; Xiaoting Lu; Jing Song; Linping Wang; Huan Li; Fangqu Liu; Yidan Zhang; Qiao Niu (Elsevier, 2021)
Aluminum is a known neurotoxin that can induce Aβ deposition and abnormal phosphorylation of tau protein, leading to Alzheimer disease (AD)-like damages such as neuronal damage and decreased learning and memory functions. In this study, we constructed a rat model of subchronic aluminum maltol exposure, and the whole-transcriptome sequencing was performed on the hippocampus of the control group and the middle-dose group. A total of 167 miRNAs, 37 lncRNAs, 256 mRNAs, and 64 circRNAs expression changed. The Kyoto Encyclopedia of Genes and Genomes showed that PI3K/AKT pathway was the most enriched pathway of DEGs, and IRS1 was the core molecule in the PPI network. circRNA/lncRNA-miRNA-mRNA networks of all DEGs, DEGs in the PI3K/AKT pathway, and IRS1 were constructed by Cytoscape. Molecular experiment results showed that aluminum inhibited the IRS1/PI3K/AKT pathway and increased the content of Aβ and tau. In addition, we also constructed an AAV intervention rat model, proving that inhibition of miR-96-5p expression might resist aluminum-induced injury by upregulating expression of IRS1. In general, these results suggest that the ceRNA networks are involved in the neurotoxic process of aluminum, providing a new strategy for studying the toxicity mechanism of aluminum and finding biological targets for the prevention and treatment of AD.